Banking in Jordan: Financing corporates and SMEs in the era of COVID-19. Evidence from the EIB bank lending survey - European Investment Bank (EIB) (European Investment Bank (EIB), 2022)
Using newly collected data from the EIB Bank Lending Survey, carried out by the EIB with support from the Central Bank of Jordan, this report focuses on cyclical and structural aspects of corporate and SME lending, and investigates the actions of Jordanian banks taken during COVID-19. The impact of the pandemic on credit supply has been relatively contained, but Covid-19 has been a game-changer for various aspects of banking, including operational activities, with strong push towards greater digitalization. On the other hand, climate risk is not yet a concern for the majority of the surveyed banks, due partly to the lack of data and resources.
Keywords: 330; banking; coronavirus disease; corporate finance; economic survey; EIB loan; environmental risk prevention; Jordan; small and medium-sized enterprises; Kreditgeschäft; Unternehmensfinanzierung; Mittelstandsfinanzierung; Jordanien